The Meaning Of Weapon Lexicons In Arabic Proverbs - Muhammad Muzaki Adnan; Siti Masyitoh; Odang Odang (UIN Sunan Gunung Djati Bandung, 2021)
This research studied the use of weapon lexicons in Arabic Proverbs (AP). The discussion aims to find the meaning interpretations of the use of weapon lexicons in AP and the moral messages reflected in there. The method used is descriptive qualitative method. The data collection was carried out by the observation method with note-taking technique. The data is obtained from the Mahfuzat Arabic Proverbs Dictionary. The results showed that there were three types of weapon used in AP, there are sword (As-saif, As-sharim), arrow (As-Sahmu, Al-Kana’in), and spear (al-Asnah). The figurative meaning of the weapon lexicons is a reflection of Arabic culture that likes to fight - in ancient times -. The moral messages contained in the AP with the weapon lexicons are 1) utilizing the time; 2) keeping the words; 3) be alert; 4) introspection; 5) creative thinking.